Impact of CSR activities towards adoption of Mobile Banking - Nguyen Van Anh; Nguyen Thi Phuong Thao (Cogent Business & Management, 2021)
The purpose of this paper is to propose and examine a conceptual model that best explains key factors influencing Vietnamese customers' intention to adopt mobile banking (m-banking). This paper examines three dimensions of Corporate Social Responsibility including Economic responsibility, Environmental responsibility and Social responsibility. Structural Equation Modeling (SEM) was conducted to analyze the data collected from the field survey questionnaires administered to a convenience sample of Vietnamese banking customers. The results showed that behavioral intention is significantly influenced by trust. Specifically, CSR initiatives play a vital role in building customer trust. Therefore, this study has attempted to fill this gap by empirically examining some of the essential factors influencing the adoption of m-banking from the Vietnamese customers' perspective. Finally, practical and theoretical implications for both Vietnamese banks and researchers in the m-banking context are also discussed in the concluding section.
Keywords: 650; CSR; Trust; Mobile banking; intention to use